Foreign direct investment vs. development assistance as tools of foreign policy Chinese policy in Africa - Květová, Lenka; Kratochvíl, Petr, 1975-; Knotková, Vladimíra; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
This thesis examines Chinese foreign direct investments in Sub-Saharan Africa and their influence on Chinese foreign policy on the continent between the years 2004 and 2010. It is often believed that oil and raw materials are the principal determinants of Chinese investments in Africa. However, this research suggests that even though there exists strong correlation between the existence of reserves of raw materials and FDI distribution, such motivation is not the only one. Pragmatism, manifested by the Chinese government in FDI allocation, can lead the People's Republic to invest in controversial countries with bad governance like Sudan. China is then forced to keep closer relations with such countries and thus promote their stability to protect its investments. Tools of such efforts include foreign policy, closer cooperation on multilateral level, which includes establishment of Forum on China-Africa Cooperation, and foreign aid.
Vedoucí práce: Petr Kratochvíl
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses